2011
DOI: 10.1007/s10067-010-1672-3
|View full text |Cite
|
Sign up to set email alerts
|

What are we doing about septic arthritis? A survey of UK-based rheumatologists and orthopedic surgeons

Abstract: This study aims to determine the current practices and beliefs of United Kingdom (UK)-based rheumatologists and orthopedic surgeons (OS) in managing septic arthritis (SA) and to determine awareness levels of national guidance. Two-hundred OS and 200 rheumatologists were sent a link to a web-based survey tool via email. Questions posed related to the management of SA, including the respondent's views on antibiotic therapy, joint drainage, which specialty should manage these cases, and also the clinician's evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…A systematic review and metaanalysis showed no difference in clinical and bacteriological effects between one antibiotic regimen and another (Bureau et al, 1999;Ravindran et al, 2009;Sammer and Shin, 2009). The choice of empirical antibiotics depends on the clinical picture, patient risk factors, and germ prevalence patterns (Butt et al, 2011;Sammer & Shin, 2009;Shirtliff and Mader, 2002). In patients at high risk of sexually transmitted diseases and staining of aspirate joints showing negative ram, ceftriaxone can be combined with azithromycin or doxycycline for eradication of Gonococcus and Chlamydia infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and metaanalysis showed no difference in clinical and bacteriological effects between one antibiotic regimen and another (Bureau et al, 1999;Ravindran et al, 2009;Sammer and Shin, 2009). The choice of empirical antibiotics depends on the clinical picture, patient risk factors, and germ prevalence patterns (Butt et al, 2011;Sammer & Shin, 2009;Shirtliff and Mader, 2002). In patients at high risk of sexually transmitted diseases and staining of aspirate joints showing negative ram, ceftriaxone can be combined with azithromycin or doxycycline for eradication of Gonococcus and Chlamydia infections.…”
Section: Discussionmentioning
confidence: 99%
“…In patients at high risk of sexually transmitted diseases and staining of aspirate joints showing negative ram, ceftriaxone can be combined with azithromycin or doxycycline for eradication of Gonococcus and Chlamydia infections. If the patient is not clear of a high risk of sexually transmitted diseases or negative ram, ceftriaxone can be combined with vancomycin (Butt et al, 2011;Sammer & Shin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy over which mode of drainage should be used. Recently, Butt et al found that 77% of rheumatologists and 66% of orthopaedic surgeons (OS) in the UK recommended surgical joint drainage; 22% and 27%, respectively, recommended repeated closed needle aspiration as their chosen method of joint drainage [35]. However, Ravindran et al, in a recent study comparing medical treatment (serial closed-needle aspiration) and surgical treatment (arthroscopy/arthrotomy combined with joint washout), showed that for native joint SA, surgical treatment was not superior to medical treatment and, therefore, highlighted the need for careful case selection for surgical intervention [36].…”
Section: Discussionmentioning
confidence: 99%
“…22% of rheumatologists and 27% of orthopedic surgeons would prefer closed-needle aspiration. Only a minority of doctors would prefer an open joint washout [43]. In reality, so far, there is no randomized controlled trial with results that can identify which method is superior [45].…”
Section: Current Treatment Of Bacterial Septic Arthritismentioning
confidence: 97%
“…However, only 7% of rheumatologists and 4% of orthopedic surgeons would continue antibiotics until inflammatory markers normalized [43].…”
Section: Current Treatment Of Bacterial Septic Arthritismentioning
confidence: 99%